2019
DOI: 10.1016/j.seppur.2018.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Mixed matrix membranes based on MIL-101 metal–organic frameworks in polymer of intrinsic microporosity PIM-1

Abstract: This work presents a study on mixed matrix membranes (MMMs) of the polymer of intrinsic microporosity PIM-1, embedding the crystalline Cr-terephthalate metal-organic framework (MOF), known as MIL-101. Different kinds of MIL-101 were used: MIL-101 with an average particle size of ca. 0.2 µm, NanoMIL-101 (ca. 50 nm), ED-MIL-101 (MIL-101 functionalized with ethylene diamine) and NH 2 -MIL-101 (MIL-101 synthesized using 2aminoterephthalic acid instead of terephthalic acid). Permeability, diffusion and solubility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 67 publications
1
47
0
Order By: Relevance
“…MMMs containing porous materials, such as zeolite [3][4][5][6] and metal organic frameworks (MOF) [7,8], have been studied to improve gas permeability and gas selectivity. Several studies have succeeded in developing gas permeation properties exceeding Robeson's upper bound [9,10]. On the other hand, it has been reported that MMMs with non-porous particles have also improved gas permeability [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…MMMs containing porous materials, such as zeolite [3][4][5][6] and metal organic frameworks (MOF) [7,8], have been studied to improve gas permeability and gas selectivity. Several studies have succeeded in developing gas permeation properties exceeding Robeson's upper bound [9,10]. On the other hand, it has been reported that MMMs with non-porous particles have also improved gas permeability [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 With different metal–organic frameworks (MOFs) introduced into PIM-1, the corresponding MMMs have shown excellent gas separation performance. 810 Particularly, the MMM based on PIM-1 and zeolitic imidazolate framework (ZIF-8), the O 2 and N 2 permeability were increased by 190 and 94%, respectively; meanwhile, the O 2 /N 2 selectivity was increased by 50%. 11 However, the poor compatibility between polymer substrates and MOF particles usually leads to nonuniform distribution of particles, especially for MMMs with high filler loading, and it may cause agglomeration and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also reported on other types of MOF/Carbon composites such as MOF-5/expanded natural graphite (ENG) (Liu et al, 2012), MIL-101(Cr)/ZTC (Musyoka et al, 2016) and HKUST-1/graphene platelets (Hassan et al, 2019). Additionally, other MOF/polymer composites such as PIM-1/MIL-101 (Cr) (Khdhayyer et al, 2019), PIM-1/UiO-66 (Khdhayyer et al, 2017), PIM-1/UiO-66-NH 2 (Tien-Binh et al, 2018), PIM-1/UiO-66- CN (Yu et al, 2019) and Matrimid/UiO-66 MMMs (Marti et al, 2018) have been reported. However, no work has been done on composites materials consisting of the three pristine materials (carbon/polymer/MOF) for H 2 adsorption applications.…”
Section: Introductionmentioning
confidence: 99%